Bilateral Chronic Subdural Nontraumatic Hematoma in a Woman Affected by AL Amyloidosis - Luongo, M.; Grassi, M.; Godano, U. (Journal of Neurological Surgery Reports, 2015)
Chronic subdural hematoma (CSDH) is a condition frequently seen in neurosurgical practice, especially among the elderly. It is often preceded by head injury, even a trivial trauma. Light chain (AL) amyloidosis is a disorder involving extracellular tissue deposition of misfolded native proteins called amyloids. The several types of amyloidosis differ by source of proteins, organ involvement, treatment, and prognosis. We describe the case of a 59-year-old woman affected by AL amyloidosis, harboring surgically treated bilateral chronic nontraumatic subdural hematoma, and we suggest a possible correlation between the clinical entities of CSDH and AL amyloidosis.
Keywords: chronic subdural hematoma; AL amyloidosis; headache; acute subdural bleeding; amyloids; vessel fragility